Pengaruh Love of Money, Persepsi Peluang Berwirausaha, dan Pengetahuan Kewirausahaan terhadap Minat Berwirausaha Mahasiswa Universitas Udayana - Putra Widiada, I Gusti Ngurah Agung Manik; Purna Anggara, I Wayan Gde Wahyu (Ekonomis: Journal of Economics and Business, 2025)
This study aims to obtain empirical evidence regarding the influence of love of money, perception of entrepreneurial opportunities, and entrepreneurial knowledge on the entrepreneurial interest of students at Udayana University. The sample used in this study was students of the 2020 intake at Udayana University with a total of 100 respondents. The sampling method used was the probability sampling method with proportionate stratified random sampling and data were collected using a questionnaire. The data analysis technique used to test the hypothesis was descriptive statistical analysis and structural equation model (SEM) based on partial least square (PLS). The results of this study revealed that simultaneously and partially there was a positive and significant influence between the variables of love of money, perception of entrepreneurial opportunities, and entrepreneurial knowledge on the variable of entrepreneurial interest of Udayana University students.